Analisis Tindakan Sosial Max Weber dalam Kebiasaan Membaca Asmaul Husna Peserta Didik MI/SD - Vivin Devi Prahesti (AN NUR: Jurnal Studi Islam, 2021)
This research aims to analyze the social action of students in elementary school about reading habits Asmaul Husna using Max Weber social action concepts. The type of research used is that library research by qualitative approach. The research techniques chosen by the researcher is documentation and analysis from a variety of books and journals or sources being relevant. The data sources are from some references to the book and journal. The finding research is social action with Max Weber theory approach becoming main references how and why students following Asmaul Husna reading habits by variety motive and purposes. The conclusion gotten by this research is that Max Weber has a strategy and social approach where the implementation of Asmaul Husna on students, students’ concept, action and tradition that have the main role in the habit processes.